SOME OBSERVATIONS ON THE APPLICATION OF MANUFACTURING EXPENSE OF PRODUCTION. - Bennett, George E. (The Accounting Review, 1926)
Abstract Many writers insist that accounting principles are fairly well standardized but a brief scrutiny of a few presumably representative publications leads to the belief that even a fair degree of standardization has not as yet been attained. A most interesting statement was noticed, for example, in a book bearing a 1925 copyright to the effect that cost of manufacture in no way is concerned with the in-process inventory either as of the beginning of the fiscal period or of its end. Moat cost systems fail because the distribution of overhead is at fault. But the situation cannot be improved to an appreciable extent by general suggestions in as much as fixed rules are impossible. In any calculation related to manufacturing expense the ultimate object is to apply such cost to the goods being produced and this application should proceed in a direct a manner as possible under the existing circumstances. The method of direct changes having been applied a fully as conditions justify, the remaining portion of cost must be allocated somehow and in the nature of the case the distribution of this balance is bound to be accomplished on a more or less arbitrary basis.